Magic Craftsmanship: A Glimpse into Bryan Cantley's Thirdspace. (1st March 2018) - Spiller, Neil
Abstract : Guest‐EditorNeil Spiller describes the work of Bryan Cantley, Professor of Design Theory at California State University Fullerton and founding spatial orchestrator of experimental research practice Form:uLA in Orange County, seeing in it Surrealist precedent and revelling in its compositional architectural and graphic opulence.